2017
DOI: 10.1021/acs.jafc.7b01693
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic β-Carotene Degradation in Provitamin A-Biofortified Crop Plants

Abstract: Provitamin A biofortification, the provision of provitamin A carotenoids through agriculture, is regarded as an effective and sustainable intervention to defeat vitamin A deficiency, representing a global health problem. This food-based intervention has been questioned in conjunction with negative outcomes for smokers and asbestos-exposed populations of the CARET and ATBC trials in which very high doses of β-carotene were supplemented. The current notion that β-carotene cleavage products (apocarotenoids) repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 65 publications
1
73
0
Order By: Relevance
“…Carotenoid accumulation depends on the regulation of key enzymes like phytoene synthase (PSY) for synthesis, chaperones like OR that stabilizes PSY improving carotenoid storage, and carotenoid cleavage dioxygenase (CCDs) involved in carotenoid degradation (L. Li, Yuan, Zeng, & Xu, 2016; Sun et al, 2018). Thus, modifying the plant carotenogenic pathway results in different carotenoid content and stability depending on the plastidial accumulating capability (Li et al, 2012; Schaub et al, 2017). Therefore, plants with lower carotenoid content in sink organs may produce higher increases when the isoprenoid pathway is modified by overexpression of carotenogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoid accumulation depends on the regulation of key enzymes like phytoene synthase (PSY) for synthesis, chaperones like OR that stabilizes PSY improving carotenoid storage, and carotenoid cleavage dioxygenase (CCDs) involved in carotenoid degradation (L. Li, Yuan, Zeng, & Xu, 2016; Sun et al, 2018). Thus, modifying the plant carotenogenic pathway results in different carotenoid content and stability depending on the plastidial accumulating capability (Li et al, 2012; Schaub et al, 2017). Therefore, plants with lower carotenoid content in sink organs may produce higher increases when the isoprenoid pathway is modified by overexpression of carotenogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Saffron has been used as colorant in foods since antiquity . Studies have also revealed the presence of other apocarotenoids in foods (including green leafy vegetables, non‐green vegetables, cereal grains, fruits, and soft drinks) although in concentrations markedly lower than those of the parent carotenoids from which they are derived . For example, apo‐6′‐, apo‐8′‐, apo‐10′‐, apo‐12′‐, and apo‐14′‐lycopenals have been detected in tomato, red grapefruit, and watermelon product, typically at concentrations ≈1000 times lower relative to lycopene .…”
Section: Importance Of Carotenoids In Agro‐food Health and Diseasementioning
confidence: 99%
“…For example, apo‐6′‐, apo‐8′‐, apo‐10′‐, apo‐12′‐, and apo‐14′‐lycopenals have been detected in tomato, red grapefruit, and watermelon product, typically at concentrations ≈1000 times lower relative to lycopene . These apocarotenoids may be formed by either enymatic cleavage and nonenzymatically …”
Section: Importance Of Carotenoids In Agro‐food Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…can also cleave all-trans--apo-10'-carotenal into the ketone β-apo-13-carotenone (d'orenone), but with low activity (13). Non-enzymatic cleavage, which occurs at each double bond in the carotenoid backbone, is another important route for apocarotenoid formation (14). This process is triggered by reactive oxygen species (ROS) and can also yield signaling molecules, such as the plant stress signal -cyclocitral, which is formed by singlet oxygen ( 1 O2) and mediates gene responses to this ROS (15).…”
Section: Introductionmentioning
confidence: 99%